PENGARUH PROBLEM BASED LEARNING BERBANTUAN VIRTUAL LABORATORY TERHADAP KETRAMPILAN PROSES SAINS DAN PENGUASAAN KONSEP SISWA DI SMA - Hendrik Siswono; Wartono Wartono; Supriyono Koes H (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2014)
This study aims to determine the effect of science process skills and conceptual understandings students through problem based learning (PBL) with real-virtual laboratory, PBL with virtual laboratory, and PBL with real laboratory. This study uses a quasi-experimental and research design with pretest-posttest control group. The study population was a class X SMAN 1 Lumajang the number of 8th grade. The samples were 6 groups of randomly selected class sampling. The first group is the experimental class 1 in 2 class which comprises treatment of PBL with real-virtual laboratory, the second group is experimental class 2 in 2 class which treated PBL with virtual laboratory, and the third group was the control class consisting of 2 classes with PBL treatment real laboratory. Data retrieval science process skills and conceptual understandings of the learning process is done through observation and multiple-choice tests that have expert validation and testing instruments. Virtual laboratory using the PhET‟s software. Analysis of the data using Analysis of Variance (ANOVA) with one lane further Kruskal-Wallis test. The results showed that : (1) Students use PBL with the real-virtual laboratory has the effect of science process skills better. (2) Students use PBL with the real-virtual laboratory give results better conceptual understandings. Keywords: problem based learning, virtual laboratory, science process skills, conceptual understandings.